PENGARUH KOMPETENSI DAN MOTIVASI PEGAWAI TERHADAP KINERJA PEGAWAI PADA PT. MADUROO INTERNASIONAL DKI. JAKARTA - Priyambada, Bagus Bima; Sudarijati, Sudarijati (JURNAL VISIONIDA, 2016)
The aim of research to determine the effect of competence and employee motivation at PT Maduroo International. Koesioner distributed to 4 supervision of each division. The questioner using validity and reliability test. Likert scale is used prior to testing with multiple regression. Results of the study of motivation and competence PT International Maduroo simultaneously have influence on employee performance. Partially flexibiltas competence, ability to learn, the desire of achievement, work on target, willingness to cooperate, customer orientation affects the performance. While intrinsic motivation in the success achieved something, recognition of work, responsibility, career advancement, professional development and intellectual and organizational policies extrinsic factors, intrapersonal relations and payroll have an influence on employee performance.Keywords: Competence, Motivation, Employee performance